Marginal Assessment of Crowns by the Aid of Parallel Radiography - Farnaz Fattahi; Rashin Giti; Kianoosh Torabi (Mashhad University of Medical Sciences, 2015)
Introduction: Marginal adaptation is the most critical item in long-term prognosis of single crowns. This study aimed to assess the marginal quality as well asthe discrepancies in marginal integrity of some PFM single crowns of posterior teeth by employing parallel radiography in Shiraz Dental School, Shiraz, Iran. Methods: In this descriptive study, parallel radiographies were taken from 200 fabricated PFM single crowns of posterior teeth after cementation and before discharging the patient. To calculate the magnification of the images, a metallic sphere with the thickness of 4 mm was placed in the direction of the crown margin on the occlusal surface. Thereafter, the horizontal and vertical space between the crown margins, the margin of preparations and also the vertical space between the crown margin and the bone crest were measured by using digital radiological software. Results: Analysis of data by descriptive statistics revealed that 75.5% and 60% of the cases had more than the acceptable space (50µm) in the vertical (130±20µm) and horizontal (90±15µm) dimensions, respectively. Moreover, 85% of patients were found to have either horizontal or vertical gap. In 77% of cases, the margins of crowns invaded the biologic width in the mesial and 70% in distal surfaces. Conclusion: Parallel radiography can be expedient in the stage of framework try-in to yield some important information that cannot be obtained by routine clinical evaluations and may improve the treatment prognosis